La Innovación Desde un Sentido Crítico, Etnometodológico y Hermenéutico (2014)
Do we know what we mean when we use the word "innovation"? This is basically a question that we should ask ourselves many times and that intellectual exercise from time to time we make it to find a stable and sustainable response from solid foundations. But forget it, and let go by the colloquial use of the term sense of innovation or anecdotal evidence daily that lets you use the terms as if it was common sense but in the background are not. This paper points to this issue. From a critical, ethnographic and hermeneutic epistemological sense and in that personal sense, reflections on the use of the term innovation are discussed. The resulting letter, written in experiential way, is a contribution to the still drawings in qualitative research studies, and a complement to formal studies in innovation, and in short is to provide a new forum for ideas on innovation at a time when the charge current term as a pillar of contemporary change and personal, national and business development.